(untitled) (International Journal of Engineering and Computer Science, 2015)
Identifying inter-frame forgery and tampering a video is a challenging topic in video forensics. Tampering involves falsification with video content in order to cause damage or make unauthorised modification/alteration. These tampering impacts need to be studied. Till now the studies employed a video authentication method that detects and determines both frame duplication and region duplication in terms of video forgery, and locates factors that impact video forgery. In this review paper all the proposed techniques based on video duplication forgery has been studied to test whether the video is real or not.